Concise Total Syntheses of Paullone and Kenpaullone via Cyanide-Catalyzed Intramolecular Imino-Stetter Reaction - Lee, Sang Eun; Lee, Seong Jong; Cheon, Cheol-Hong (Synthesis, 2017)
Highly concise total syntheses of paullone and kenpaullone were developed. Cyanide-catalyzed intramolecular imino-Stetter reaction of aldimines derived from methyl 2-aminocinnamate derivatives and 2-nitrobenzaldehyde provided 2-(2′-nitrophenyl)indole-3-acetic acid derivatives. Subsequent reduction of the nitro group with zinc under acidic conditions to an amino group followed by spontaneous lactam formation allowed for the total syntheses of paullone and kenpaullone to be completed in two steps starting from commercially available materials. The direct use of a nitro group as the precursor of an amino group present in the phenyl ring at the 2-position in the indole ring significantly streamlined the total syntheses of these target molecules.
Keywords: paullone; kenpaullone; total synthesis; cyanide-catalyzed imino-Stetter reaction; umpolung of aldimines